Dampak Keterampilan Literasi Digital dan Optimalisasi Peran Orang Tua terhadap Minat Baca Peserta Didik Sekolah Dasar - Zasmita, Indah; Nirmala, Sri Dewi; Patiro, Shine Pintor Siolemba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the relationship between parental role and digital literacy skills and the reading interest of elementary school students in Lubuk Linggau City, both partially and simultaneously. The method used in this study was a quantitative approach with a correlational design and a questionnaire as the research instrument. The results showed that parental role had a value (t-count = 5.018), while hypothesis testing showed that digital literacy skills had a value (t-count = 5.047). The results for the multiple effects obtained a value of F-count > F-table (64.517 > 3.04). The conclusion of this study indicates that parental role and digital literacy skills simultaneously positively affect the reading interest of elementary school students in Lubuk Linggau City. Keywords: Digital Literacy Skills, Reading Interest, Parental Role